Critical friends - real time insights for shaping strategy - and Johnson, Debbie; Nathan, Geeta; Rahman, Syahirah Abdul (Chapters, 2022)
This chapter focuses on facilitation given by the Innovation Caucus to provide expert academic critique to inform Innovate UK's strategy for UK business innovation. As Innovate UK's strategy developed, it became evident that several policy domains needed critical insights and evidence. An academic critical friend provided the latest academic insights, evidence and wider perspective of the actors in the UK Innovation system, insights of which policy makers often lack. The chapter gave case studies of Innovation Caucus' work with Innovate UK in facilitating extensive research expertise and helping policy makers to open dialogue. It also describes 'The Innovators' Breakfast Club', a webinar series organised by Innovation Caucus, co-developed with Innovate UK, which created live face-to-face dialogue between academic experts and Innovate UK strategy/policy leads. This example showed how critical friends are important in facilitating the initial dialogues needed to build evidence for policy making. The dialogue builds the foundation for a virtuous cycle of learning. The approach provides an opportunity for academic experts to gain insights into the priorities and dilemmas facing policy makers, to shape future academic research and refine the skill set needed to become critical friends.